SURVEY KUALITAS TIDUR DAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI WILAYAH KERJA PUSKESMAS TARUS KECAMATAN KUPANG TENGAH - Flegon Hermes Anin (CHMK Applied Science Journal, 2019)
Hypertension is a condition when blood pressure in blood vessels increases chronically. According to the AHA (American Heart Association) in 2011, in America, 59% of people with hypertension were only 34% under control. Riskesdas data (2013) of 15 million hypertensive sufferers, 50% of hypertension has not been controlled. The results of riskesdas (2013) in NTT the prevalence of hypertension is 7.2% and is below the national rate of 9.4%. Kota Kupang health service (2016) the number of hypertensive patients in Kupang City Sikumana Health Center was 85 people. Alcohol consumption is a risk factor that can cause hypertension. This study aims to determine the relationship between the history of consuming alcohol and hypertension in the Sikumana Health Center in Kupang City. The design in this study is analytic internationally with case control research design. The sample in this study amounted to 118 people, divided into 2 by the control group of 59 people and the case group of 59 people, using purposive samplingtechnique. Instrument research uses questionnaires and uses a blood pressure measuring device. This study was analyzed using spearman rho. The results showed that there was no relationship between alcohol consumption and hypertension, with significant values of spearman rho p = 0.130 (p> 0.05). Researchers suggest that health care staff in Kupang City Sikumana Health Center often provide information or counseling about hypertension and the causes of hypertension. Keywords: History of Alcohol Consumption, Hypertension